The Relationship Between Creativity and the Learning Outcomes of Written Batik for Class XI Students at SMK Negeri 8 Padang - Rahmi, Fathiah (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2025)
This study focuses on how students' creativity can affect their learning outcomes, which is caused by several factors, namely students being passive in learning, relying on friends for skills, being lazy in doing assignments, and postponing practical assignments. The purpose of this study is to determine the relationship between creativity and learning outcomes of batik tulis students in class XI of SMK Negeri 8 Padang and how significant the relationship is. In this study, a correlation test was used to identify the relationship between creativity and learning outcomes of students in class XI of SMK Negeri 8 Padang, in order to determine the significance between creativity and learning outcomes. The data sources used are primary data, namely data taken directly from respondents through filling out questionnaires prepared in accordance with the problem under study, namely about student creativity in written batik lessons, while secondary data is a source of data obtained by researchers indirectly through intermediaries, namely values obtained from teachers and school administration. Data analysis and hypothesis testing were carried out using SPSS version 25. The results of this study after conducting a correlation test on data obtained through questionnaires and student learning outcomes for 1 semester showed that there was no significant relationship between creativity and learning outcomes with a Pearson Correlation value (0.198). The effect of creativity on the learning outcomes of writing batik students in class XI SMK Negeri 8 Padang was recorded at 3.9%.